Effect of Feeding Maize (Zea mays) Husk and Cob Based Complete Feed Block on Feed Intake, Nutrient Utilization and Growth in Mandya Sheep - Shashikumar, M. G.; Prabhu, T. M.; Gloridoss, R. G.; Singh, K. Chandrapal; Suresh, B. N.; Siddalingamurthy, H. K.; Manjunatha, S. S. (Indian Journal of Animal Nutrition, 2017)
The present study was conducted to compare the conventional finger millet (Eleucine coracana) strawbased complete feed block (CFB) with maize (Zea mays) husk and cob based complete feed block on the growthperformance of lambs. Twenty Mandya/Bannur lambs of about 4 to 6 months of age with body weight rangingfrom 8 to 14 kg were divided into two groups of ten each in a completely randomized design. The CFB withfinger millet straw was fed to group T1 and maize husk and cob was fed in group T2. A six days digestion trial wasconducted at the end of the experiment. Maize husk and cob was comparable with finger millet straw except forlower CP (2.82 vs. 5.98). Cumulative gas (mL/200 mg DM/24 h) production and energy density (ME MJ/kg DM)was higher in maize husk and cob as compared to finger millet straw (35.83 vs. 32.66; 7.23 vs. 6.99). There was nosignificant difference in DMI between the groups. A significant difference was observed in OM, NDF and ADFintake between the groups. The ADG (g) and FCR (g DMI/g body weight gain) were also similar in both thegroups. The digestibility of nutrients was comparable between the groups. It could be concluded that the maizehusk and cob can be utilized as a roughage component of complete feed block for feeding small ruminantsunder intensive production system.